Cor triatriatum dexter with underdevelopment of the right ventricle – case report - Karolczak, Maciej A.; Mądry, Wojciech; Werner, Bożena; Godlewski, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
A case of a 1.5-year-old boy with cyanotic form of cor triatriatum dexter with underdevelopment of the right ventricle is presented in detail. The authors discuss embryology, diagnostics and haemodynamics of this rare heart defect.